2020
DOI: 10.1007/s00395-020-00829-5
|View full text |Cite
|
Sign up to set email alerts
|

Mouse models of atherosclerosis and their suitability for the study of myocardial infarction

Abstract: Atherosclerotic plaques impair vascular function and can lead to arterial obstruction and tissue ischaemia. Rupture of an atherosclerotic plaque within a coronary artery can result in an acute myocardial infarction, which is responsible for significant morbidity and mortality worldwide. Prompt reperfusion can salvage some of the ischaemic territory, but ischaemia and reperfusion (IR) still causes substantial injury and is, therefore, a therapeutic target for further infarct limitation. Numerous cardioprotectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 235 publications
(293 reference statements)
1
38
0
1
Order By: Relevance
“…One of the main important limitations of the current study regards the difficulty of transferring rodent atherosclerosis phenotypes to a human setting, as most rodent models of atherosclerosis do not completely mimic the pathophysiology of the atherosclerotic artery in human. It is reported that atherosclerotic plaques could frequently be manifested in the wall of the aorta as well as the large vessels, and seldom affect the coronary arteries as in humans [ 56 , 57 ]. Consequently, the validity of the rat model of atherosclerosis used in the current study is highly acceptable at the level of large blood vessels, but not at the level of small blood vessels, which needs a different study model for addressing them.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main important limitations of the current study regards the difficulty of transferring rodent atherosclerosis phenotypes to a human setting, as most rodent models of atherosclerosis do not completely mimic the pathophysiology of the atherosclerotic artery in human. It is reported that atherosclerotic plaques could frequently be manifested in the wall of the aorta as well as the large vessels, and seldom affect the coronary arteries as in humans [ 56 , 57 ]. Consequently, the validity of the rat model of atherosclerosis used in the current study is highly acceptable at the level of large blood vessels, but not at the level of small blood vessels, which needs a different study model for addressing them.…”
Section: Discussionmentioning
confidence: 99%
“…Small mammalian animals such as rabbits and mice are cheaper to rear, and mice can be easily manipulated genetically ( Mushenkova et al, 2019 ; Poznyak et al, 2020 ). However, long-term fat-fed rabbits are prone to hepatotoxicity and a severe inflammatory response, and the plasma lipid profiles differ considerably among inbred strains of mice and also among different mouse mutants, rendering large variation in their susceptibility to AS ( Paigen et al, 1985 ; Getz and Reardon, 2012 ; Fan et al, 2015 ; Golforoush et al, 2020 ; Vedder et al, 2020 ). Thus, no single animal model is sufficient for AS research; therefore, additional novel animal models are required.…”
Section: Introductionmentioning
confidence: 99%
“…The macrophages that have differentiated in the sub-endothelium then phagocytose Ox-LDL via the Ox-LDL receptors CD36 and SR-A, and when Ox-LDL breaks down within the cells it accumulates intracellularly as cholesterol esters 17 , 18 . Repeated phagocytosis causes the macrophages to become hypertrophic, transforming them into foamy macrophages; this is defined as fatty streak 17 19 . Fatty streak proceeds to the formation of fibrous plaque and advanced plaque, which shows infiltration of smooth muscle cells and accumulation of extracellular matrix, and release of matrix metalloproteinases, respectively 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Repeated phagocytosis causes the macrophages to become hypertrophic, transforming them into foamy macrophages; this is defined as fatty streak 17 19 . Fatty streak proceeds to the formation of fibrous plaque and advanced plaque, which shows infiltration of smooth muscle cells and accumulation of extracellular matrix, and release of matrix metalloproteinases, respectively 19 . Finally, degradation of the extracellular matrix by metalloproteinases increases plaque vulnerability and their breakdown leads to the formation of blood clots that occlude the vessel and obstruct blood flow, causing acute myocardial infarction, cerebral infarction, and other forms of cardiovascular disease 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation